2018
DOI: 10.1111/psyg.12326
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of older psychiatric patients and their caregivers towards electroconvulsive therapy

Abstract: Clinicians in Chinese psychiatric hospitals need to provide sufficient information on ECT to older patients and their caregivers before treatment, particularly regarding the treatment process and adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 34 publications
2
14
0
12
Order By: Relevance
“…Although ECT was generally viewed as beneficial, effective, and safe, memory impairment was its most commonly reported adverse effect. 14,32 The present study showed a significant difference in knowledge and attitude scores after video-assisted teaching program (P < 0.001). These findings are corroborated by several other studies that assessed the effect of educational intervention using the video among various groups such as caregivers, health care professionals, and the general public.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Although ECT was generally viewed as beneficial, effective, and safe, memory impairment was its most commonly reported adverse effect. 14,32 The present study showed a significant difference in knowledge and attitude scores after video-assisted teaching program (P < 0.001). These findings are corroborated by several other studies that assessed the effect of educational intervention using the video among various groups such as caregivers, health care professionals, and the general public.…”
Section: Discussionmentioning
confidence: 46%
“…These findings are corroborated by several other studies that assessed the effect of educational intervention using the video among various groups such as caregivers, health care professionals, and the general public. 11,31,14 Review of literature suggested that educational videos and pamphlets increased the knowledge and promoted a favorable and neutral attitude toward ECT. 18 The present study also got similar findings by using video-assisted teaching combined with handouts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All data analyses were performed using the Comprehensive Meta‐Analysis software (CMA Version 2.0; Biostat, 2005). In the case of three studies (Jiao, Wang, Zhou, Bai, & Li, 2017; Li et al, 2016; Zhang et al, 2018) which examined MHL in both patients and caregivers, data for each sample group contributed to the analyses independently (Lipsey & Wilson, 2001). To avoid bias, for 10 studies (Chen et al, 2011; Chen & Tan, 2010; Chen, Zuo, & Shen, 2008; Ding & Chen, 2012; Huang, 2013; Jin, Zhang, Wang, & Duan, 2006; Liu, 2009; Tan, 2005; Xing & Kang, 2017; Xing, Xi, & Xu, 2002) which investigated participants' MHL before and after an intervention, only the data obtained before the intervention were utilized.…”
Section: Methodsmentioning
confidence: 99%
“…The psychoeducation needs to be performed in each technique and approach in order to avoid miss understand which brings worries in caregivers and could influence the burnout. The study of knowledge of Electro conversion therapy ( ETC) shown that caregivers needs necessary information when an approach that concerns them is being used therefore this would be taken in consideration as an intervention technic that would help caregivers and patients in general [38].…”
Section: Intervention Care and Mental Health Knowledge For Caregiversmentioning
confidence: 99%